The Communicative Approach to Form Metalinguistic Competencies of Students of Non-Philological Majors - Gordiienko, Yulia (Pedagogical Discourse, 2022)
Having taken practices of the Department of Languages at Comenius University in Bratislava as an example, the article considers the content and ways to form metalinguistic competences of students of non-philological majors which are supposed to boost graduates’ adaptation to dynamic changes of political, economic, and sociocultural space in the globalized world. Methodologically, the research is based on the interdisciplinary concept which interprets synergetic effects of cross-disciplinary data of theoretical and applied linguistics, sociolinguistics, multilingualism, psychology, and communication development, along with research on intercultural communication which lead to new and effective ways of interpreting linguistic phenomena in educational and situational contexts of learning a foreign language. The conclusion is made that the communicative approach serves to form speaking, reading and writing skills of the students of non-philological majors through choosing the writing register, interpreting senses, and semantic analysis of lexical units in the appropriate context. The situational dependence of educational activities is an effective means of speech motivation which provides the necessary communicative novelty to develop the ability to combine, and proactively speak, etc. It means that the final communicative goal is determined by forming students’ metalinguistic competences which are characterized by syntactic, discourse and social relevance and appropriateness. It should be noted that the communicative approach makes it possible to vary different dominant ideas and procedures; additionally, it correlates with the concept of freedom, relating to the choice of means and methods of teaching, and, also, the formation of a free personality who can perceive the world in all its complexity and diversity.